Abordagem semiclássica para uma carga pontual sob a influência de potenciais anarmônicos e do inverso do quadrado atrativo - Veloso, Jardel de Carvalho (2023)
We apply the WKB approximation to the Schrödinger equation of a point charge under the influence of anharmonic potentials and attractive inverse-square potential in order to calculate the allowed energies for the particle. These potentials arise from the interaction of a point charge with non-uniform radial electric fields in cylindrical symmetry. For the potentials that arise from these interactions we consider the bound states for the particular case of s-waves.